Acute Effects of Foam Rolling on Hamstrings After Half-Marathon: A Muscle Functional Magnetic Resonance Imaging Study - Shu, Dingbo; Zhang, Chuan; Dai, Siyu; Wang, Shubo; Liu, Jie; Ding, Jianping (Frontiers in Physiology, 2021)
Foam rolling (FR) is widely used for post-exercise muscle recovery; yet, the effects of FR on skeletal muscle inflammation and microvascular perfusion following prolonged exercise are poorly understood. We aim to address the gap in knowledge by using magnetic resonance imaging T2 mapping and intravoxel incoherent motion sequences to study the acute effects of FR on hamstring following half-marathon running in recreational runners. Sixteen recreational marathon runners without lower extremity injury were recruited. After half-marathon running, FR was performed on the hamstring muscles on the dominant side, while the other limb served as a control. MRI T2 and IVIM scans were performed bilaterally at baseline (pre-run), 2-3 hours after running (post-run), immediately after FR (post-FR0), 30 minutes after FR (post-FR30) and 60 minutes after FR (post-FR60). T2, a marker for inflammatory edema, as well as IVIM microvascular perfusion fraction index f for hamstring muscles were determined. Total Quality Recovery scale score was also collected. Both T2 and f were higher at post-run compared to pre-run in all hamstring muscles on both sides (p < 0.05). For the FR side, T2 and f changed significantly at post-FR0 and post-FR30 compared to post-run in all muscles (p < 0.05) except for f at BFL and SM at post-FR30 (both p > 0.05), although f at BFL was still marginally elevated at post-FR30 (p = 0.074). Both parameters for all muscles returned to post-run level at post-FR60 (p > 0.05) except for T2 at SM (p = 0.037). In contrast, most MRI parameters were not changed at post-FR0, post-FR30 and post-FR60 compared to post-run for the control side (p < 0.05). TQR scores were elevated at post-FR0 and post-FR30 compared to post-run (both p < 0.05), and returned to the post-run level at post-FR60 (p > 0.99).Hamstring inflammatory edema and microvascular perfusion were elevated following half-marathon running, which were detectable with MRI T2 mapping and IVIM sequences. FR resulted in acute alleviation in inflammation and greater microvascular perfusion; however, the effects seemed to last only for a short period of time (30min-60min). FR can provide short-term benefits to skeletal muscle after prolonged running.